Quality of Life Indicators and Policy Strategies to Advance Sustainability in the Pearl River Delta - Knopman, Debra (RAND Corporation, 2015)
This report proposes a system of quality of life indicators and identifies policy options to advance sustainability in the Pearl River Delta, a region of Guangdong Province in southeastern China. The report focuses on land use and transportation goals and strategies, with additional analysis of policies related to the environment, housing, and economic development.